Social isolation and its impact on child and adolescent development: a systematic review - Isabelle Lina de Laia Almeida; Jaqueline Ferraz Rego; Amanda Carvalho Girardi Teixeira; Marília Rodrigues Moreira (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: This study aims to analyze the effects of social isolation on children's and teenagers' development, with emphasis on the possible impacts over their physical and mental health. Data source: Review of the literature following the standards of PRISMA using the SciELO, LILACS and PubMed databases. The following key-words were used: "social isolation" and "child development", "quarantine" and "adolescent development" according to the Medical Subject Headings (MESH) and their translation to the Portuguese. Studies in English, Portuguese and Spanish from inception were included. Data synthesis: 519 studies were screened and 12 were included in the systematic review. Five of those focused the psychology and social issues, two of them the effects of pandemics on these issues; four studies reported on impacts on general health and two consequences over the hypothalamus- hypophysis - adrenal axis and the cognitive and social development. Conclusions: The review shows a strong association between social isolation and anxiety and depression in children and adolescents. Social isolation leads to higher levels of cortisol and worse cognitive development. Therefore, the mental and physical health of children and adolescents need a careful follow up by health professionals during and after the COVID-19 pandemic.